Plataforma Digital de Arquitectura: O repensar da tradição e promoção da arquitectura através do uso das novas tecnologias - Lucas Rafael Belinha Pereira (2019)
The present theoretical-practical research explores the possibility of approaching architecture, constructionand the public through the use of new digital technologies in representation and communication.The reflection of the methods of representation and communication of these threeareas of study represent the cause of the construction of a digital platform that aspires to be theunion of these three realities and that will be reflected in the structure of this same dissertation.This dissertation is divided into four phases. The first phase consists of the historical contextualizationof the current digital culture and its influence on the discipline of architecture. The second andthird phase consist of a reflection on the representation and communication systems of the threeresearch areas - Architecture, Construction and the Public - that identify and theorize the technologicalmeans of representation and communication (manual) and contemporary (digital) architecturalprojects, construction products and the dissemination of the properties of the general population.Relativethe the methods of representing the architecture and construction in the manual, it portraysthe transposition of orality into writing, from writing to drawing, drawing as a method (the plan,the section, the elevation and the constructive detail), the emergence of three-dimensional space(the perspective and axonometry) and the respective materiality of these methods (the models).In the methods of representation of the architecture and the construction in the digital, it consistsin the transfer of this method to the digital (the computer-aided design- CAD), theemergence of the three-dimensional space in the digital (BIM), the materiality of the methodin digital (the models), the search for reality in the digital (virtual reality) and the search fornew methods in this new digital culture (3D modeling and virtual reality on the internet).Relativethe the methods of representing the public in the manual, it portrays the understandingof its method, from the writing to the graphic element. That is, its cadastralrepresentation and its origin, the cartographic bases, the first letters, the military letter,the geometric register of rustic property and the birth of the architectural intermediary.In the method of representation of the public in the digital, it consists in the use of geographicinformation systems (GIS), the new technological tools used for cadastral representation(SINERGIC) and the understanding of the digital architectural intermediary.The reflection of these methods is the cause of the fourth phase, the digital platform Archiprojectwhich consists of the rethinking of representation and communication of architecture, constructionand the public through the use of new digital technologies. In the first part, we have the requirementssurvey that includes the interviewing of people connected to the three areas of study and the casestudies - existing digital platforms. And, finally, the systematization of this reflection, its the conceptualizationand implementation of the prototype of the digital platform Archiproject as a means ofdigital representation and online communication that seeks to impart new elements.